Soil erosion hazard and mitigation in the Euro-Mediterranean region: do we need more research? - Poesen, Jean (Hungarian Geographical Bulletin, 2015)
Soil erosion represents a geomorphological and geological hazard that may cause property damage, loss of livelihoods and services, social and economic disruption, or environmental damage. Erosion of our soils not only lowers the quality of soils on site, resulting in a drastic reduction of their ecosystem functions that play a vital role in daily life, but causes also signifi cant sediment-related problems off site. To curb soil erosion problems, a range of soil conservation techniques and strategies are applied. So far, ca. 7,000 papers on soil erosion and ca. 15,000 papers on soil conservation in the Euro-Mediterranean region have been published (Web of Science, 2015). One might therefore conclude that we now know almost everything about the various soil erosion processes, their factors and consequences as well as their control so that little new knowledge can still be added to the vast amount of available information. We refute this conclusion by pointing to some major research gaps that need to be addressed if we want to use our soils in the Anthropocene in a more sustainable way and improve environmental conditions worldwide. More specifi cally the following research needs are addressed: 1) improved understanding of soil erosion processes and their interactions, 2) scaling up soil erosion processes and rates in space and time, 3) innovative techniques and strategies to prevent or reduce erosion rates.